Baicalin From Scutellaria baicalensis Impairs Th1 Polarization Through Inhibition of Dendritic Cell Maturation - Mi Eun Kim; Hyung Keun Kim; Hyeon-Young Park; Dae Hyun Kim; Hae Young Chung; Jun Sik Lee (Elsevier, 2013)
Baicalin from Scutellaria baicalensis is a major flavonoid constituent found in the traditional Chinese medicinal herb Baikal skull cap. It has been widely used for the treatment of various diseases such as pneumonia, diarrhea, and hepatitis. Recent studies have demonstrated that baicalin possesses a wide range of pharmacological and biological activities, including anti-inflammatory, anti-microbial, anti-oxidant, and anti-tumor properties. Specifically, its antiinflammatory activity has been estimated in various animal models of acute and chronic inflammation; however, its effects on dendritic cells (DCs) maturation and immuno-stimulatory activities are still unknown. In this study, we attempted to determine whether baicalin could influence DC surface molecule expression, antigen uptake capacity, cytokine production, and capacity to induce T-cell differentiation. Baicalin was shown to significantly suppress the expression of surface molecules CD80, CD86, major histocompatibility complex (MHC) class I, and MHC class II as well as the levels of interleukin-12 production in lipopolysaccharide stimulated DCs. Moreover, baicalin-treated DCs showed an impaired induction of the T helper type 1 immune response and a normal cell-mediated immune response. These findings provide important understanding of the immunopharmacological functions of baicalin and have ramifications for the development of therapeutic adjuvants for the treatment of DCs-related acute and chronic diseases. Keywords:: baicalin, dendritic cell, cytokine, Th1 polarization